Still life - McDermid, Val (McDermid, Val. Karen Pirie novel., 2020)
"The UK's "Queen of Crime" Val McDermid returns to her propulsive series featuring cold case detective Karen Pirie, who finds herself investigating the shadowy world of forgery, where things are never what they seem. Still Life is intensely gripping from the first page and further proof that McDermid is writing at the top of her game. When a lobster fisherman on an early morning run pulls in his traps, he finds something he wasn't expecting to catch-a body. Turns out the dead man was the brother of a senior Scottish government official who vanished without a trace, and Detective Chief Inspector Karen Pirie is asked to take over the investigation. At the same time, a woman in the wealthy enclave of Perth is clearing out her sister's home after a fatal road accident and finds a mysterious camper van in the garage containing a skeletonized body. But who is it? And how long has it been there? The two cases will draw Karen into the world of imposters, identity theft, and art forgery"--